Age differences in proactive coping with minor hassles in daily life - Neubauer, Andreas B.; Smyth, Joshua M.; Sliwinski, Martin J. (The journals of gerontology. Series B, Psychological sciences, social sciences, 2019)
Objectives - Age differences in the exposure to minor hassles in daily life have been postulated by socioemotional selectivity theory and reported by previous research, with older adults reporting fewer stressors. The present study examined two potential mechanisms explaining this reduction in reported stressor exposure with advancing age: age-related changes in proactive coping and in the threshold of labeling an event as stressor. - - Method - Participants (N = 178; 20-79 years; M = 49.5; SD = 17; 51% female) were investigated in a measurement burst study consisting of three measurement bursts (each comprised of five daily assessments for 7 consecutive days), separated by 9 months each. - - Results - Older age was unrelated to reporting an event or the thresholds for labeling the event as a stressor, but was positively related to self-reported use of proactive coping and negatively related to reported event severity. - - Discussion - Results are consistent with the view that older adults engage in more proactive coping to deal with minor hassles in their daily lives to manage these problems before they become more stressful. Older adults did not report fewer potentially stressful events but they reported these events as less unpleasant. The adaptive value of proactive coping, in particular for older adults, is discussed.
Advance access publication June 21, 201
Gesehen am 24.03.2021